Santa cruise - Michaels, Fern (Kensington Publishing Corp., 2021)
Reuniting for a state-of-the-art cruise during the holidays--one with hundreds of eligible men--four best friends cheer each other on through speed-dating events and shore excursions, but soon discover things not going as planned as they set sail on surprising new adventures.